Stand by me - Simmons, Pat, 1959- (Family is forever, 2021)
"Romantic Christian women's fiction by acclaimed author Pat Simmons explores faith and love. Kym Knicely thought her days as a caregiver were over. But once she starts falling for family man Chaz Banks, caregiver to his seven year-old autistic granddaughter, Kym will need to make some sacrifices to get the family she always wanted"--